Improving information evaluation for intelligence production. Issue 4 (7th June 2019) - Irwin, Daniel; Mandel, David R.
ABSTRACT: National security decision-making is informed by intelligence assessments, which in turn depend on sound information evaluation. We critically examine information evaluation methods, arguing that they mask rather than effectively guide subjectivity in intelligence assessment. Drawing on the guidance metaphor, we propose that rigid 'all-purpose' information evaluation methods be replaced by flexible 'context-sensitive' guidelines aimed at improving the soundness, precision, accuracy and clarity of irreducibly subjective judgments. Specific guidelines, supported by empirical evidence, include use of numeric probability estimates to quantify the judged likelihood of information accuracy, promoting collector-analyst collaboration and periodic revaluation of information as new information is acquired.